Le vie chirurgiche di accesso al ginocchio posteriore in traumatologia - Bove, F.; Capitani, P.; Calabrò, F.; Capitani, D. (Lo Scalpello - Journal, 2018)
POSTERIOR SURGICAL APPROACHES TO THE KNEE IN TRAUMATOLOGYThere are multiple surgical approaches to the posterior part of the tibia. In the management of complex fractures ofthe tibial plateau that involve the posterior part, surgeons must be familiar with all the surgical approaches to obtainthe best result. A preoperative plan including X-rays, CT scan and clinical evaluation is mandatory to choose the bestsurgical approaches for each patient.